2021
DOI: 10.1021/acs.jpcc.1c04205
|View full text |Cite
|
Sign up to set email alerts
|

Fluence-Dependent Transient Reflectance of Stainless Steel Investigated by Ultrafast Imaging Pump–Probe Reflectometry

Abstract: The ablation efficiency during laser processing strongly depends on the initial and transient reflectance of the irradiated material surface. This article reports on the transient relative change of the reflectance ΔR/R of stainless steel during and after ultrashort pulsed laser excitation (800 nm, 40 fs) by spatially resolved pump–probe reflectometry. The spatial resolution of the setup in combination with the spatial Gaussian intensity distribution of the pump radiation enables a fluence-resolved detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…2 b, both Bessel and Gaussian beams resulted in similar tendencies of ablation efficiency, with the peak of (mm /min W) corresponding to the fluence window of 0.5–1 J/cm . This range is accompanied by visible effects of excitation on the transient optical properties 54 , 55 . This peak efficiency window was in line with the numerical optimization model for Gaussian beams reported by Neuenschwander et al 56 , 57 that proposes a rule of thumb definition of the optimal fluence for efficient use of photons in the case of Gaussian beams .…”
Section: Resultsmentioning
confidence: 98%
“…2 b, both Bessel and Gaussian beams resulted in similar tendencies of ablation efficiency, with the peak of (mm /min W) corresponding to the fluence window of 0.5–1 J/cm . This range is accompanied by visible effects of excitation on the transient optical properties 54 , 55 . This peak efficiency window was in line with the numerical optimization model for Gaussian beams reported by Neuenschwander et al 56 , 57 that proposes a rule of thumb definition of the optimal fluence for efficient use of photons in the case of Gaussian beams .…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure 4a, the local fluence that induces the second ablation region was 0.87 J/cm 2 , approximately twice the Si ablation threshold (0.43 J/cm 2 ). The previous inves tigations on different materials also identifies two distinctive regions for the laser-induced modifications, and found that the threshold for the second region was approximately twice the threshold for the first region [33,34].…”
Section: Ablation Dynamics Observation and Analysismentioning
confidence: 86%
“…This cavity leads to a phase shift between the probe radiation being partially reflected on the delaminated and remaining material, which can lead to the evolution of Newton rings. [13,14,30] Since the surfaces of both films have not been modified after irradiation, the oscillating reflectance in the center of the irradiated area between 10 ps <t < 500 ps results from a temporary delamination with a subsequent reattachment of the films. Because ablation is not the scope of this study, the evolution of ΔR/R in the center is not considered more detailed in the following considerations.…”
Section: Temporal Evolution Of the Laser-induced Transient Reflectancementioning
confidence: 99%
“…[8][9][10] These alterations to the functional material properties described above can be induced by single-pulsed femtosecond (fs) laser irradiation [9] and can be tracked in the ultrafast time regime by applying pump-probe metrology. [11][12][13][14][15] This approach provides insights into the pathways leading to lattice reordering. However, whereas single fs pulses have been applied to selected systems, the broader scope of the transformations in lattice order remains an open question, for example, the effect of single fs laser pulsing on different types of positional and chemical order and crucially, the time scales at which transformations can be realized.…”
Section: Introductionmentioning
confidence: 99%